Market reaction to capital expenditures of powerful CEOs - Boumosleh, Anwar (2011)
Anwar Boumosleh holds a PhD in Finance from the University of Alabama. He has been teaching MBA Corporate Finance and Investments since joining LAU in 2005. He also taught at the University of Central Florida. His research interest is in corporate finance; specifically, corporate governance and CEO and director compensation. He is also a CFA and has worked in the Lebanese banking industry. Elias Raad holds an MBA from the University of Dallas and a PhD in Finance from the University of Alabama. Currently, he is a faculty of finance at the Lebanese American University in Beirut Lebanon, the Chairperson of the Finance and Accounting Department, and the Director of the Executive MBA programme. He has published in the areas of banking, mergers and acquisitions, and insider trading.